Pengaruh Lingkungan Belajar terhadap Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran Biologi di Kelas MIPA SMA Negeri 20 Pangkep - Ridha Ulfitrah Hamzah; Irmawanty Irmawanty; Hilmi Hambali (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This type of research is survey research. The purpose of this research is to (1) determine the influence of the learning environment on learning motivation, (2) determine the influence of the learning environment on learning outcomes. The population in this study were all MIPA class students at SMAN 20 Pangkep and the selected sample was 144 students. The data collection techniques in this research were questionnaires and documentation. The collected data was then analyzed using descriptive statistical analysis and inferential statistics. The research results show that there is a positive and significant influence between the learning environment on learning motivation. This was proven in testing the t-test hypothesis, which obtained a value of 9,366 with a significance level of 0.000 < 0.05. So it can be concluded that the learning environment plays an important role in the ongoing learning process, especially in student learning motivation. There is a positive and significant influence between the learning environment on learning outcomes. This was proven in testing the t-test hypothesis, which obtained a value of 9,683 with a significance level of 0.000 < 0.05. So it can be concluded that the learning environment plays an important role in the ongoing learning process, especially in student learning outcomes.